Cell culture models to study retinal pigment epithelium-related pathogenesis in age-related macular degeneration. (September 2022) - Bharti, Kapil; den Hollander, Anneke I.; Lakkaraju, Aparna; Sinha, Debasish; Williams, David S.; Finnemann, Silvia C.; Bowes-Rickman, Catherine; Malek, Goldis; D'Amore, Patricia A.
Abstract: Age-related macular degeneration (AMD) is a disease that affects the macula – the central part of the retina. It is a leading cause of irreversible vision loss in the elderly. AMD onset is marked by the presence of lipid- and protein-rich extracellular deposits beneath the retinal pigment epithelium (RPE), a monolayer of polarized, pigmented epithelial cells located between the photoreceptors and the choroidal blood supply. Progression of AMD to the late nonexudative "dry" stage of AMD, also called geographic atrophy, is linked to progressive loss of areas of the RPE, photoreceptors, and underlying choriocapillaris leading to a severe decline in patients' vision. Differential susceptibility of macular RPE in AMD and the lack of an anatomical macula in most lab animal models has promoted the use of in vitro models of the RPE. In addition, the need for high throughput platforms to test potential therapies has driven the creation and characterization of in vitro model systems that recapitulate morphologic and functional abnormalities associated with human AMD. These models range from spontaneously formed cell line ARPE19, immortalized cell lines such as hTERT-RPE1, RPE-J, and D407, to primary human (fetal or adult) or animal (mouse and pig) RPE cells, and embryonic and induced pluripotent stem cell (iPSC) derived RPE. Hallmark RPE phenotypes, such as cobblestone morphology, pigmentation, and polarization, vary significantly betweendifferent models and culture conditions used in different labs, which would directly impact their usability for investigating different aspects of AMD biology. Here the AMD Disease Models task group of the Ryan Initiative for Macular Research (RIMR) provides a summary of several currently used in vitro RPE models, historical aspects of their development, RPE phenotypes that are attainable in these models, their ability to model different aspects of AMD pathophysiology, and pros/cons for their use in the RPE and AMD fields. In addition, due to the burgeoning use of iPSC derived RPE cells, the critical need for developing standards for differentiating and rigorously characterizing RPE cell appearance, morphology, and function are discussed. Highlights: In vitro models of the RPE provide a powerful tool to study RPE biology and AMD pathogenesis. Key hallmarks of AMD pathophysiology have been replicated in several in vitro models. Primary RPE and RPE cell lines are easily accessible and useful in biochemical and cell biology studies. iPSC-derived RPE have been validated to present native-RPE like features and can provide patient-specific models. Organ-on-chips and 3D organoids provide physiologically relevant models combining RPE with other ocular cell types.